Bio-based polycarboxylic acid anti-wrinkle finishing agent as well as preparation method and application thereof
By using bio-based polycarboxylic acid anti-wrinkle finishing agent in cotton fabrics, the problem of cotton fabrics being prone to wrinkles is solved, and the effect of small amount, good washing resistance and long-lasting wrinkle resistance is achieved.
Patent Information
- Application Number
- CN202411592338.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
Cotton fabrics are prone to wrinkles due to hydrogen bond fractures in cellulose molecules and relative slippage of macromolecular chain segments. The existing anti-wrinkle finishing agents are deficient in large amounts, poor washing resistance, and insufficient wrinkle resistance.
Using bio-based polycarboxylic acid anti-wrinkle finishing agent, its molecular structure contains 2,5-cyclohexanedione structure and multiple carboxyl groups, the addition reaction, saponification and acidification treatment are carried out under the action of catalyst and phase transfer agent to prepare the High wrinkle resistance product.
This anti-wrinkle finishing agent not only has good wrinkle recovery performance, but also has a small amount, good washing fastness, and has a long-lasting anti-wrinkle performance, which significantly improves the comfort of cotton fabrics.
Smart Images

Figure CN119462357A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bio-based polycarboxylic acid anti-wrinkle finishing agent and a preparation method and application thereof, belonging to the technical field of textile auxiliaries. Background Art
[0002] With the improvement of people's living standards, people's requirements for textiles are not limited to good-looking styles and low prices, but also pursue comfort, health, environmental protection and other requirements. Cotton fabrics are popular because of their comfortable feel, good moisture absorption and breathability, anti-static and affordable prices. However, cotton fabrics have disadvantages such as poor elasticity and easy wrinkles. They cannot maintain a flat appearance during wearing, which greatly reduces the wearing experience. To improve the disadvantage of cotton fabrics that they are prone to wrinkles, anti-wrinkle finishing can be achieved in post-finishing.
[0003] There are many hydroxyl groups in cellulose molecules. When subjected to external forces, hydrogen bonds between cellulose molecules gradually break and the chain segments move relative to each other, and then new hydrogen bonds can be generated at new positions. When external forces act, the breaking process of intermolecular bonds is very intense and the newly formed hydrogen bonds are also very strong, causing cellulose fibers to deform in a way that is difficult to recover, and eventually causing cotton fabrics to wrinkle. The fundamental reason for wrinkles in fabrics is the breaking of hydrogen bonds, the relative slippage of macromolecular segments, and the formation of new hydrogen bonds at new positions. Therefore, anti-wrinkle treatment of fabrics can be solved from these three aspects. The breaking and formation of hydrogen bonds are relatively difficult to control. The existing anti-wrinkle principles and anti-wrinkle finishing agents are proposed and developed to prevent the relative slippage between macromolecular segments. The existing anti-wrinkle mechanisms only have the resin deposition theory and the covalent cross-linking theory.
[0004] The resin deposition theory holds that thermosetting small molecule resin particles or monomers diffuse into the amorphous region of the fiber, self-condense under high temperature to form a network structure deposition, and the deposited resin limits the relative slippage between the fiber macromolecular segments through physical-mechanical effects. Based on this principle, many polymer resins are widely used in the research of anti-wrinkle finishing agents. Common formaldehyde-containing anti-wrinkle finishing agents, such as urea-formaldehyde resin, melamine formaldehyde resin, 2D resin (DMDHEU), as well as some water-based polyurethanes, polyacrylate emulsions, etc., are anti-wrinkle finishing agents developed based on this mechanism.
[0005] The covalent cross-linking theory holds that a cross-linking agent containing two or more active groups can react with the hydroxyl groups on the cotton fiber to form covalent cross-links, thereby increasing the degree of interconnection between cellulose macromolecular chains and enhancing the ability of cellulose macromolecules to resist external forces together. Usually, small-molecule anti-wrinkle finishing agents are easier to enter the interior of the fiber and form covalent cross-links with the fiber. For example, polycarboxylic acid anti-wrinkle finishing agents such as citric acid, 1,2,3,4-butanetetracarboxylic acid (BTCA) and phosphorus-containing polycarboxylic acid 2-phosphinobutane-1,2,4 tricarboxylic acid (PBTCA) are developed based on this mechanism. It is generally believed that polycarboxylic acids can undergo esterification reaction with cellulose to form ester bonds between molecules, thereby achieving an anti-wrinkle effect.
[0006] When polymer anti-wrinkle finishing agents with reactive groups in their structure act on cotton fibers, two mechanisms, resin deposition and covalent cross-linking, will occur simultaneously. The finishing effects will be different depending on the proportion of the two.
[0007] At present, it is found that polycarboxylic acids that can react with cotton fabrics to make them wrinkle-resistant include butanetetracarboxylic acid (BTCA), citric acid (CA), trisaccharide, malic acid, polymaleic acid, maleic acid, cyclopentanetetracarboxylic acid, tartaric acid, mellitic acid, maleic acid-acrylic acid-vinyl alcohol copolymer, maleic acid-itaconic acid copolymer, etc. In general, polycarboxylic acid compounds need to add catalysts to react with cotton fabrics under high-temperature baking conditions. A large number of studies have shown that polycarboxylic acids are the most promising formaldehyde-free anti-wrinkle finishing agents, among which BTCA finishing agent has the best effect and the most mature process. The DP grade (Durable Press, durable pressure grade) of cotton fabrics finished with it can reach 4 to 5, and the washing resistance is good, but BTCA is expensive and the finishing cost is high. CA is also a polycarboxylic acid that has been studied more. It is cheap and the raw materials are easy to obtain, but the finishing effect is not as good as BTCA, and the finished fabrics are seriously yellowed. The main reason for the yellowing of fabrics finished with CA is that when CA is baked at high temperature, the hydroxyl groups in the molecule will dehydrate to form aconitic acid. Aconitic acid itself is yellow, which causes the finished fabrics to turn yellow.
[0008] Wang Guowei et al. studied the anti-wrinkle effect of polycarboxylic acid DEMA (Wang Guowei, Zhuang Linghua. Synthesis of polycarboxylic acid anti-wrinkle finishing agent DEMA. Printing and Dyeing Auxiliary Agents, 2006, 23(11):3) and polycarboxylic acid DEMB with 6 carboxyl groups (Wang Guowei, Zhuang Linghua, Xu Jing et al. Synthesis and application of polycarboxylic acid anti-wrinkle finishing agent DEMB; Printing and Dyeing Auxiliary Agents, 2008, 25(7):25-27) on cotton fabrics. The structural formulas of DEMA and DEMB are shown below. They are obtained by Michael addition reaction of acrylate with malonic acid diester and itaconate with malonic acid diester and then hydrolyzed.
[0009] The structural formula of DEMA:
[0010] The structural formula of DEMB:
[0011] Although the above polycarboxylic acids can play a certain anti-wrinkle effect, because these polycarboxylic acids are aliphatic polycarboxylic acids (except mellitic acid), their molecular structures lack units with strong rigidity and planarity, such as cyclohexyl ring, benzene ring, naphthalene ring, furan ring or tetrahydrofuran ring, etc., so their anti-wrinkle effect is limited. Although trimellitic anhydride, pyromellitic dianhydride or mellitic acid have benzene ring structures in their molecular structures, the degradability and biosafety of the benzene ring are poor, and the acidity is extremely strong, which easily causes the strength loss of cotton fabrics. Summary of the invention
[0012] The purpose of the present invention is to provide a bio-based polycarboxylic acid anti-wrinkle finishing agent and a preparation method and application thereof. The prepared bio-based polycarboxylic acid anti-wrinkle finishing agent not only has good wrinkle recovery performance when used for anti-wrinkle finishing of fabrics, but also has the advantages of small dosage, good washing fastness and long-lasting anti-wrinkle performance.
[0013] In order to achieve the above object, the technical solution adopted by the present invention is:
[0014] A bio-based polycarboxylic acid anti-wrinkle finishing agent has a 2,5-cyclohexanedione structure in its molecular structure, and a plurality of carboxyl groups are directly and / or indirectly grafted onto the six-membered carbon ring of the 2,5-cyclohexanedione, and the number of the grafted carboxyl groups is 2-8.
[0015] Preferably, the finishing agent has a structure shown in Formula I or Formula II:
[0016]
[0017] The preparation method of the above-mentioned bio-based polycarboxylic acid anti-wrinkle finishing agent is to carry out an addition reaction between dimethyl succinylsuccinate and methyl acrylate or dimethyl itaconate in the presence of a catalyst and a phase transfer agent to obtain an addition product, and then saponify and acidify the obtained addition product.
[0018] Preferably, the specific method for preparing the addition product by addition reaction is: adding a solvent, a catalyst, a phase transfer agent, dimethyl succinylsuccinate and methyl acrylate or dimethyl itaconate into a container, refluxing at 100-125° C. for 1-5 hours, then removing unreacted components and solvent under reduced pressure, and then filtering, washing, drying and recrystallizing to obtain the addition product.
[0019] Preferably, the catalyst is sodium carbonate or potassium carbonate.
[0020] Preferably, the phase transfer agent is PEG400 or PEG1000 or PEG2000.
[0021] Preferably, the addition ratio of the catalyst, the phase transfer agent, dimethyl succinylsuccinate and methyl acrylate or dimethyl itaconate is (0.05-20) g: (1-20) g: (0.05-0.5) mol: (0.1-2) mol.
[0022] Preferably, the solvent used for the addition reaction is n-hexane, cyclohexane or toluene.
[0023] Preferably, the specific method of saponification is: mixing the addition product with an alkali solution having a concentration of 10-40% at a ratio of 1 g: (40-60) mL, and stirring at 35-50° C. for 20-40 h.
[0024] Preferably, the specific method of acidification is: after saponification, vacuum rotary evaporation is performed to obtain a concentrated solution, and then an acid solution with a concentration of 5-20% is added to adjust the pH of the concentrated solution to 2-4, crystallization is precipitated at 0-10°C, and the crystals are filtered to obtain a bio-based polycarboxylic acid anti-wrinkle finishing agent.
[0025] The application of the above-mentioned bio-based polycarboxylic acid anti-wrinkle finishing agent in anti-wrinkle finishing of fabrics comprises the following steps:
[0026] S1. preparing an anti-wrinkle finishing liquid: dissolving a bio-based polycarboxylic acid anti-wrinkle finishing agent in water to prepare a 3-20% solution, and then mixing a catalyst to obtain an anti-wrinkle finishing liquid; wherein the catalyst is any one of sodium hypophosphite, sodium hydrogen phosphite, sodium dihydrogen phosphite, sodium dihydrogen phosphate and disodium dihydrogen pyrophosphate, and the catalyst concentration is 0.2-0.7%;
[0027] S2. Immerse the fabric in the anti-wrinkle finishing liquid, and perform immersion treatment with a rolling rate of 85-95%; pre-dry at 90-120°C for 1-5 minutes, and then bake at 140-180°C for 1-5 minutes; wash with water, and then dry at 70-90°C for 3-10 minutes; then adjust the fabric to moisture.
[0028] The beneficial effects of the present invention are:
[0029] The molecular structure of the bio-based polycarboxylic acid anti-wrinkle finishing agent contains a 2,5-cyclohexanedione structure, which not only provides a certain rigidity to the polycarboxylic acid molecule, increases the glass transition temperature of the resin after the polycarboxylic acid molecule is cross-linked with cellulose, and improves the anti-wrinkle performance, but also has two carbonyl groups that can condense with other functional groups (such as amino, methyl, methylene, etc.), which can further increase the cross-linking between the polycarboxylic acid compound and cellulose, increase the cross-linking density between the resin and cellulose, and increase the anti-wrinkle performance. The anti-wrinkle finishing of cotton fabrics using the provided bio-based polycarboxylic acid anti-wrinkle finishing agent not only has good wrinkle recovery performance, but also has the advantages of small dosage, good wash fastness, and long-lasting anti-wrinkle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is the HNMR spectrum of the product of Michael addition reaction of DMSS and methyl acrylate;
[0031] Figure 2 is the HNMR spectrum of anti-wrinkle finishing agent I;
[0032] Figure 3 is the HNMR spectrum of the product of Michael addition reaction of DMSS and dimethyl itaconate;
[0033] Figure 4 This is the HNMR spectrum of anti-wrinkle finishing agent II. DETAILED DESCRIPTION
[0034] The bio-based high-performance anti-wrinkle finishing agent provided in the present application has the structure shown in I or II below:
[0035] Bio-based anti-wrinkle finishing agent I:
[0036]
[0037] Bio-based anti-wrinkle finishing agent II:
[0038]
[0039] The preparation method of polycarboxylic acid anti-wrinkle finishing agent I mainly comprises the following two steps:
[0040] (1) Dimethyl succinylsuccinate (DMSS) reacts with methyl acrylate in a solvent in the presence of an alkaline catalyst and a phase transfer agent to produce a Michael addition product, dimethyl bis(methyl propionate) succinylsuccinate (BMP-DMSS); the reaction formula is as follows:
[0041]
[0042] (2) The dimethyl bis(methyl propionate) succinylsuccinate (BMP-DMSS) obtained in the reaction in (1) is hydrolyzed (saponification reaction) under alkaline conditions (sodium hydroxide solution) to generate a tetracarboxylic acid sodium salt, which is then acidified under acidic conditions (dilute hydrochloric acid or dilute sulfuric acid), concentrated, cooled, and crystallized to obtain an anti-wrinkle finishing agent I; the reaction formula is as follows:
[0043]
[0044] In the preparation process, the solvent used in the first step reaction is any one of n-hexane, cyclohexane and toluene; the alkaline catalyst used is sodium carbonate or potassium carbonate; and the phase transfer agent is any one of PEG400, PEG1000 and PEG2000.
[0045] The preparation method of polycarboxylic acid anti-wrinkle finishing agent II mainly consists of the following two steps:
[0046] (1) Dimethyl succinylsuccinate reacts with dimethyl itaconate in a solvent in the presence of an alkaline catalyst and a phase transfer agent to produce a Michael addition product, dimethyl bis(succinate dimethyl methyl) succinylsuccinate (BDMMS-DMSS); the reaction formula is as follows:
[0047]
[0048] (2) The dimethyl bis(succinate dimethyl methyl) succinylsuccinate (BDMMS-DMSS) obtained in the reaction (1) is hydrolyzed (saponification reaction) under alkaline conditions to generate hexacarboxylic acid sodium salt, which is then acidified under acidic conditions, concentrated, cooled and crystallized to obtain an anti-wrinkle finishing agent II; the reaction formula is as follows:
[0049]
[0050] In the preparation process, the solvent used in the first step reaction is any one of n-hexane, cyclohexane and toluene; the alkaline catalyst used is sodium carbonate or potassium carbonate; and the phase transfer agent is any one of PEG400, PEG1000 and PEG2000.
[0051] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0052] Example 1
[0053] (a) Preparation of dimethyl bis(methyl propionate) succinylsuccinate (BMP-DMSS)
[0054] In a 500ml four-necked flask, 22.8g (0.1mol) of dimethyl succinylsuccinate (DMSS, produced by Sinopharm Group), 200ml of anhydrous n-hexane, 0.1g of potassium carbonate, 2g of PEG1000 and 25.8g (0.3mol) of methyl acrylate were added. After reflux at 80°C for 3 hours, the excess methyl acrylate and solvent cyclohexane were removed under reduced pressure, and then 300ml of deionized water was added to the four-necked flask, shaken, washed and filtered, and the filter cake was washed 3 times with deionized water and then dried. The dried filter cake was recrystallized with anhydrous ethanol to obtain 35g of dimethyl bis(methyl propionate) succinylsuccinate (BMP-DMSS), with a yield of 87.5%. The HNMR of the product is shown in the attached figure. Figure 1 . 1HNMR (400MHz, DMSO) δ3.75 (s, 3H, -OCH3); δ3.55 (s, 3H, -OCH3); δ3.07 (s, 2H, -CCH2CO); δ2.35 (t, 2H, -CH2CH2COOCH3); δ2.25 (t, 2H, -CH2CH2COOCH3).
[0055] (b) Preparation of Anti-wrinkle Finishing Agent I
[0056] 150 ml of 20% sodium hydroxide solution was added to a 500 ml four-necked flask equipped with a condenser, and 30 g of BMP-DMSS prepared in step (a) was added while stirring. The mixture was kept warm and stirred at 40°C for 24 hours, and then concentrated to a volume of 100 ml by rotary evaporation under reduced pressure. A 10% hydrochloric acid solution was added dropwise to the concentrated solution to adjust its pH to 3. The neutralized solution was then placed in a refrigerator and kept warm at 3°C overnight. Crystals precipitated in the bottle, and 30.64 g of crystals were obtained by filtration, with a yield of 80.0%, which was anti-wrinkle finishing agent I. The HNMR of the product is shown in the attached figure. Figure 2 . 1 HNMR (400MHz, DMSO) δ11.95 (s, 2H, -COOH); δ3.05 (s, 2H, -CCH2CO); δ2.33 (t, 2H, -CH2CH2COOH); δ2.01 (t, 2H, -CH2CH2COOH).
[0057] Example 2
[0058] (a) Preparation of dimethyl bis(methyl propionate) succinylsuccinate (BMP-DMSS)
[0059] In a 1000ml four-necked flask, 68.4g (0.3mol) of dimethyl succinate (DMSS, produced by Sinopharm Group), 200ml of anhydrous toluene, 10g of potassium carbonate, 10g of PEG400 and 86.0g (1mol) of methyl acrylate were added. After reflux at 110°C for 3 hours, the excess methyl acrylate and solvent toluene were removed under reduced pressure, and then 300ml of deionized water was added to the four-necked flask, shaken, washed and filtered, and the filter cake was washed with deionized water 3 times and then dried. The dried filter cake was recrystallized with anhydrous ethanol to obtain 101g of dimethyl bis(methyl propionate) succinate (BMP-DMSS), with a yield of 83%.
[0060] (b) Preparation of Anti-wrinkle Finishing Agent I
[0061] In a 1000ml four-necked flask equipped with a condenser, 500ml of 20% sodium hydroxide solution was added, and 101g of BMP-DMSS prepared in step (a) was added while stirring. The mixture was kept warm and stirred at 40-45°C for 24 hours, and then concentrated to a solution volume of 300ml by rotary evaporation under reduced pressure. A 10% hydrochloric acid solution was added dropwise to the concentrated solution to adjust its pH to 3. The neutralized solution was then placed in a refrigerator and kept warm at 3°C overnight. Crystals precipitated in the bottle, and 80g of the crystals were obtained by filtration with a yield of 93%, which was an anti-wrinkle finishing agent I.
[0062] Example 3
[0063] (a) Preparation of dimethyl bis(methyl propionate) succinylsuccinate (BMP-DMSS)
[0064] In a 1000ml four-necked flask, 68.4g (0.3mol) of dimethyl succinate (DMSS, produced by Sinopharm Group), 200ml of anhydrous cyclohexane, 10g of potassium carbonate, 10g of PEG2000 and 86.0g (1mol) of methyl acrylate were added. After reflux at 80°C for 3 hours, the excess methyl acrylate and solvent cyclohexane were removed under reduced pressure, and then 300ml of deionized water was added to the four-necked flask, shaken, washed and filtered, and the filter cake was washed with deionized water 3 times and then dried. The dried filter cake was recrystallized with anhydrous ethanol to obtain 101g of dimethyl bis(methyl propionate) succinate (BMP-DMSS), with a yield of 83%.
[0065] (b) Preparation of Anti-wrinkle Finishing Agent I
[0066] In a 1000ml four-necked flask equipped with a condenser, 500ml of 20% sodium hydroxide solution was added, and 101g of BMP-DMSS prepared in step (a) was added while stirring. The mixture was kept warm and stirred at 40-45°C for 24 hours, and then concentrated to a solution volume of 300ml by rotary evaporation under reduced pressure. A 10% hydrochloric acid solution was added dropwise to the concentrated solution to adjust its pH to 3. The neutralized solution was then placed in a refrigerator and kept warm at 3°C overnight. Crystals precipitated in the bottle, and 80g of the crystals were obtained by filtration with a yield of 93%, which was an anti-wrinkle finishing agent I.
[0067] Example 4
[0068] (a) Preparation of dimethyl bis(succinate dimethyl methyl) succinylsuccinate (BDMMS-DMSS)
[0069] In a 1000ml four-necked flask, 68.4g (0.3mol) of dimethyl succinylsuccinate (DMSS, produced by Sinopharm Group), 200ml of anhydrous cyclohexane, 10g of potassium carbonate, 10g of PEG2000 and 158.0g (1mol) of dimethyl itaconate were added. After reflux at 80°C for 3 hours, the excess dimethyl itaconate and solvent cyclohexane were removed under reduced pressure, and then 300ml of deionized water was added to the four-necked flask, shaken, washed and filtered, and the filter cake was washed with deionized water 3 times and then dried. The dried filter cake was recrystallized with anhydrous ethanol to obtain 151g of bis(dimethyl succinate methyl) succinylsuccinate (BDMMS-DMSS), with a yield of 93%. The HNMR of the product BDMMS-DMSS is attached. Figure 3 .
[0070] (b) Preparation of Anti-wrinkle Finishing Agent II
[0071] In a 1000ml four-necked flask equipped with a condenser, add 500ml of 20% sodium hydroxide solution, add 150g of BDMMS-DMSS prepared in step (a) while stirring, keep warm and stir at 40-45°C for 24 hours, then evaporate under reduced pressure to concentrate to a solution volume of 300ml, add 10% hydrochloric acid solution dropwise to the concentrate to adjust its pH to 3, then put the neutralized solution into a refrigerator and keep warm at 3°C overnight, crystals precipitate in the bottle, filter to obtain 101g of crystals, with a yield of 80%, which is the anti-wrinkle finishing agent II. The HNMR of the anti-wrinkle finishing agent II is shown in the attached Figure 4 .
[0072] Example 5
[0073] (a) Preparation of dimethyl bis(succinate dimethyl methyl) succinylsuccinate (BDMMS-DMSS)
[0074] In a 2000ml four-necked flask, 102.6g (0.45mol) of dimethyl succinate (DMSS, produced by Sinopharm Group), 500ml of anhydrous n-hexane, 20g of sodium carbonate, 20g of PEG400 and 237.0g (1.5mol) of dimethyl itaconate were added. After reflux at 70°C for 3 hours, the excess dimethyl itaconate and the solvent n-hexane were removed under reduced pressure, and then 500ml of deionized water was added to the four-necked flask, shaken, washed and filtered, and the filter cake was washed 3 times with deionized water and then dried. The dried filter cake was recrystallized with anhydrous ethanol to obtain 230g of bis (dimethyl succinate methyl) succinate dimethyl succinate (BDMMS-DMSS), with a yield of 94.6%.
[0075] (b) Preparation of Anti-wrinkle Finishing Agent II
[0076] In a 2000ml four-necked flask equipped with a condenser, add 1000ml of 30% sodium hydroxide solution, add 200g of BDMMS-DMSS prepared in step (a) while stirring, keep warm and stir at 40-45°C for 24 hours, then evaporate under reduced pressure to concentrate the solution to 500ml, add 10% hydrochloric acid solution dropwise to the concentrate to adjust its pH to 3, then put the neutralized solution into a refrigerator and keep it warm at 3°C overnight, crystals precipitate in the bottle, filter and obtain 145g of crystals with a yield of 84.5%, which is anti-wrinkle finishing agent II.
[0077] Example 6
[0078] (a) Preparation of dimethyl bis(succinate dimethyl methyl) succinylsuccinate (BDMMS-DMSS)
[0079] In a 500ml four-necked flask, 22.8g (0.1mol) of dimethyl succinate (DMSS, produced by Sinopharm Group), 100ml of anhydrous toluene, 2g of potassium carbonate, 2g of PEG2000 and 80.0g (0.5mol) of dimethyl itaconate were added. After reflux at 110°C for 3 hours, the excess dimethyl itaconate and solvent toluene were removed under reduced pressure, and then 100ml of deionized water was added to the four-necked flask, shaken, washed and filtered, and the filter cake was washed with deionized water 3 times and then dried. The dried filter cake was recrystallized with anhydrous ethanol to obtain 45g of bis (dimethyl succinate methyl) succinate dimethyl succinate (BDMMS-DMSS), with a yield of 90.4%.
[0080] (b) Preparation of Anti-wrinkle Finishing Agent II
[0081] In a 1000ml four-necked flask equipped with a condenser, add 500ml of 20% sodium hydroxide solution, and add 45g of BDMMS-DMSS prepared in Example 6(a) while stirring. Keep warm and stir at 40-45°C for 24 hours, then evaporate under reduced pressure to concentrate the solution to 300ml. Add 10% hydrochloric acid solution dropwise to the concentrate to adjust its pH to 3, then put the neutralized solution in a refrigerator and keep it warm at 3°C overnight. Crystals precipitate in the bottle, and filter to obtain 101g of crystals with a yield of 80%, which is anti-wrinkle finishing agent II.
[0082] Performance Testing
[0083] The application and testing of the bio-based anti-wrinkle finishing agent obtained in the above examples can be referred to the literature "Study on Process Optimization and Reaction Kinetics of Anti-wrinkle Finishing of Cotton Fabrics with Polycarboxylic Acid" (Chu Xudong, Master's Thesis of Qingdao University, 2019). The details are as follows:
[0084] Anti-wrinkle finishing liquid configuration:
[0085] The bio-based polycarboxylic acid anti-wrinkle finishing agent I or II is directly dissolved in deionized water with vigorous stirring (500-1000 rpm) by a stirrer to prepare a 10% finishing agent solution, and a catalyst sodium hypophosphite (NaH2PO2) is added to the solution at a catalyst concentration of 0.5%.
[0086] Anti-wrinkle finishing process:
[0087] Cotton fabric (pure cotton bleached poplin (105g / m 2 ) is immersed in the finishing liquid, double-immersed and double-rolled, the rolling rate is (90%), and then pre-dried at 100°C for 2 minutes in a drying machine, and then baked at 160°C for 3 minutes, and then washed with water (refer to AATCC TestMethod124-2001 standard, rinsed in 50°C standard soap solution for 30 minutes and rinsed with water), and then dried (80°C, 5min), the dried fabric is placed in a standard atmospheric balance box (temperature 21±1°C, relative humidity 65±5%) for 24h to adjust the humidity, and the wrinkle-resistant finished cotton fabric is obtained.
[0088] Anti-wrinkle effect test:
[0089] Wrinkle recovery angle
[0090] The test was conducted in accordance with AATCC 66-2008 "Fabric Wrinkle Recovery: Recovery Angle Method". The sample size was 40 mm × 15 mm, with six warps and six wefts, and the test was conducted after balancing for at least 4 hours at a temperature of (21+1)°C and a relative humidity of (65±2)%. The warp and weft data were averaged, and the wrinkle recovery angle (warp + weft) was used as an indicator of the fabric's wrinkle recovery performance. The test equipment was the MOO3A wrinkle recovery angle tester (SDL Atlas).
[0091] Tearing strength
[0092] The test was conducted according to ASTM D 1424-1996 (Determination of the tearing strength of fabrics by the impact pendulum method). The sample size was 80 mm to 63 mm, with five warps and five wefts, and the average value was taken. Test equipment: YG033A drop-hammer fabric tear tester (Wenzhou Baien Instrument Co., Ltd.).
[0093] Whiteness
[0094] The color was measured using the Datacolor 600 computer color measurement and matching system in accordance with AATCC110--2005 (Determination of Whiteness of Textiles). Test equipment: Datacolor 600 (Datacolor Corporation).
[0095] The anti-wrinkle performance of anti-wrinkle finishing agent I and anti-wrinkle finishing agent II at different concentrations, the test results are shown in Table 1.
[0096] Table 1 Comparison of test results of bio-based polycarboxylic acid anti-wrinkle finishing agent and polycarboxylic acid BTCA
[0097]
[0098]
[0099] It can be seen from Table 1 that at a concentration of 5%, the wrinkle recovery angle of anti-wrinkle finishing agent I is 156.8°, which is much larger than BTCA's 142.3°. Although both are tetracarboxylic acid compounds, the molecular structure of anti-wrinkle finishing agent I has a rigid six-membered ring structure, while BTCA only has an alkyl structure, which is flexible and thus affects the anti-wrinkle performance.
[0100] The wrinkle recovery angle of anti-wrinkle finishing agent II at only 5% concentration is 226.9°, which is higher than the wrinkle recovery angle after finishing with 15% concentration of BTCA. This is mainly because the molecular structure of anti-wrinkle finishing agent II has a rigid six-membered ring structure and six carboxylic acid groups, and the probability of forming esterification cross-linking is higher, so the wrinkle recovery angle after finishing is larger.
[0101] In terms of tear strength retention and whiteness, the whiteness and tear strength retention of the finishing agent decrease with the increase of the finishing agent dosage. Among them, under the same dosage conditions, the tension retention of BTCA is worse than that of anti-wrinkle finishing agent I, but better than that of anti-wrinkle finishing agent II. This is mainly related to the pH value of the finishing agent. BTCA and anti-wrinkle finishing agent I have the same carboxyl content, and the pH value is similar after they are prepared into finishing agent solutions.
[0102] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A bio-based polycarboxylic acid anti-wrinkle finishing agent, characterized in that: The finishing agent has a 2,5-cyclohexanedione structure in its molecular structure, and a plurality of carboxyl groups are directly and / or indirectly grafted onto the six-membered carbon ring of the 2,5-cyclohexanedione, and the number of the grafted carboxyl groups is 2-8.
2. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 1, characterized in that: The method is to carry out addition reaction of dimethyl succinylsuccinate with methyl acrylate or dimethyl itaconate under the action of a catalyst and a phase transfer agent to obtain an addition product, and then the obtained addition product is saponified and acidified to obtain the product.
3. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 2, characterized in that: The specific method for preparing the addition product by addition reaction is: adding solvent, catalyst, phase transfer agent, dimethyl succinylsuccinate and methyl acrylate or dimethyl itaconate into a container, refluxing at 100-125°C for 1-5h, then removing unreacted components and solvent under reduced pressure, and then filtering, washing, drying and recrystallizing to obtain the addition product.
4. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 2, characterized in that: The catalyst is sodium carbonate or potassium carbonate.
5. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 2, characterized in that: The phase transfer agent is PEG400, PEG1000 or PEG2000.
6. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 2, characterized in that: The addition ratio of the catalyst, the phase transfer agent, the dimethyl succinylsuccinate and the methyl acrylate or dimethyl itaconate is (0.05-20) g: (1-20) g: (0.05-0.5) mol: (0.1-2) mol.
7. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 3, characterized in that: The solvent used for the addition reaction is n-hexane, cyclohexane or toluene.
8. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 2, characterized in that: The specific method of saponification is: after mixing the addition product with alkali solution with a concentration of 10-40% in a ratio of 1g: (40-60)ml, stirring at 35-50°C for 20-40h.
9. The method for preparing the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 8, characterized in that: The specific method of acidification is: after saponification, vacuum rotary evaporation is performed to obtain a concentrated solution, and then an acid solution with a concentration of 5-20% is added to adjust the pH of the concentrated solution to 2-4, crystallization is precipitated at 0-10°C, and the crystals are filtered to obtain a bio-based polycarboxylic acid anti-wrinkle finishing agent.
10. Use of the bio-based polycarboxylic acid anti-wrinkle finishing agent according to claim 1 in anti-wrinkle finishing of fabrics, characterized in that: The steps include: S1. preparing an anti-wrinkle finishing liquid: dissolving a bio-based polycarboxylic acid anti-wrinkle finishing agent in water to prepare a 3-20% solution, and then mixing a catalyst to obtain an anti-wrinkle finishing liquid; wherein the catalyst is any one of sodium hypophosphite, sodium hydrogen phosphite, sodium dihydrogen phosphite, sodium dihydrogen phosphate and disodium dihydrogen pyrophosphate, and the catalyst concentration is 0.2-0.7%; S2. Immerse the fabric in the anti-wrinkle finishing liquid, and perform immersion treatment with a rolling rate of 85-95%; pre-dry at 90-120°C for 1-5 minutes, and then bake at 140-180°C for 1-5 minutes; wash with water, and then dry at 70-90°C for 3-10 minutes; then adjust the fabric to moisture.
Citation Information
Cited By
Carboxymethyl cellulose filtrate reducer and preparation method thereof
CN121949689A